2022
DOI: 10.32479/ijeep.13170
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Environmental Disclosure? Evidence from Mining Companies Listed on The Indonesia Stock Exchange

Abstract: This study aims to analyse the effects of environmental performance, profitability, and leverage on the environmental disclosure in mining industry sector companies listed on the Indonesia Stock Exchange. The sample of this study was 15 mining companies which were selected by using a purposive sampling technique. We collected the company's annual report over the period 2014 – 2021. The results showed that environmental performance had a positive and significant effect on environmental disclosure. In this case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Profitability was found by (Abdullah et al, 2020;Asrori et al, 2019;Maulia and Yanto, 2020;Purbawangsa et al, 2020) to be able to improve environmental disclosure practices. On the other hand (Digdowiseiso et al, 2022) found that profitability weakens environmental disclosure practices or does not have a significant correlation with environmental disclosure (Ardi and Yulianto, 2020;Junita and Yulianto, 2018;Safitri and Wahyuningrum, 2021;Solikhah and Maulina, 2021;. Leverage, which shows the company's financial condition, is known to have a negative effect (Ardi and Yulianto, 2020;Digdowiseiso et al, 2022), but several studies have found that leverage has no effect at all (Solikhah and Maulina, 2021;Solikhah et al, 2021;.…”
Section: Environmental Disclosuresmentioning
confidence: 99%
“…Profitability was found by (Abdullah et al, 2020;Asrori et al, 2019;Maulia and Yanto, 2020;Purbawangsa et al, 2020) to be able to improve environmental disclosure practices. On the other hand (Digdowiseiso et al, 2022) found that profitability weakens environmental disclosure practices or does not have a significant correlation with environmental disclosure (Ardi and Yulianto, 2020;Junita and Yulianto, 2018;Safitri and Wahyuningrum, 2021;Solikhah and Maulina, 2021;. Leverage, which shows the company's financial condition, is known to have a negative effect (Ardi and Yulianto, 2020;Digdowiseiso et al, 2022), but several studies have found that leverage has no effect at all (Solikhah and Maulina, 2021;Solikhah et al, 2021;.…”
Section: Environmental Disclosuresmentioning
confidence: 99%
“…The highest score of environmental reporting is shown by PT BISI International, Tbk, which is engaged in seeds and trading of corn, vegetables and fruits, and rice seeds. The average score of environmental reporting in the agricultural industry is 34 percent, which is higher than those in the manufacturing industry (about 13 percent) [17], [22], in all listed companies in IDX ( about 9 percent) [24], and in mining companies (about 29 percent) [15].…”
Section: Descriptive Statisticmentioning
confidence: 99%
“…Numerous researches on environmental disclosures have been done in underdeveloped nations, for instance, India [10,11], Malaysia [12,13], Ghana [14], and Indonesia [15][16][17][18][19]. According to these studies, the investigated variables among the determinants of environmental reporting are, among others, financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the company's leverage level, the higher creditors' expectations of company performance, including its environmental performance, because environmental performance has an impact on the sustainability of company operations (Digdowiseiso et al, 2022). Companies with high leverage will result in management to reduce costs in disclosing information.…”
Section: Effect Of Leverage On Carbon Emissions Disclosurementioning
confidence: 99%